Kinetics and Mechanism of Oxidation of Methyl Ethyl Ketone by N-Bromophthalimide in Acid Medium - Ramesh, A.; Syamasundar, B.; Radhakrishna Murti, P.S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of methyl ethyl ketone by N-bromophthalimide in acetic acid-perchloric acid mixture has been studied. The reaction is first order in methyl ethyl ketone, first order in H+ and zero order in N-bromophthalimide, indicating the acid catalyzed enolization of ketone as the rate determining step and the reaction between enol and N-bromophthalimide as the fast step. Arrhenius parameters have been computed. Addition of sodium perchlorate has no effect in the reaction rate indicates the absence of ionic salt effect. Addition of added Br–, there is no acceleration in the reaction rate indicating the molecular bromine is not formed during the course of the reaction.